Users of the Public Bathhouse of Alcântara: health profile diagnosis - Figueiredo, Amélia Simões (2021)
Background: The community outreach project of the Universidade Católica Portuguesa, which involves the public bathhouse of Alcântara, started out of the need to identify its users. Objectives: To characterize the users’ socio-demographic and health profile and describe their use of social and health resources. Methodology: A cross-sectional descriptive study, of quantitative nature, was conducted with the application of a questionnaire to a sample of 145 participants. Results: The typical user is male, single, aged 25-35 years and lives alone (21%). This user goes to the public bathhouse two to three times per week. Most of the users (58.3%) have no bathroom, 29.7% are homeless, 35.2% are not registered in any health care center, and 24.8% have mental disorders. Conclusion: The typical bathhouse user is of working age, was born in Lisbon and in the Portuguese-speaking African Countries, and has no source of income. The main reasons leading to the use of the public bathhouse are the economic difficulties, the homeless condition, and the lack of sanitary conditions.